Expression of the Gene for Autotransporter AutB of Neisseria meningitidis Affects Biofilm Formation and Epithelial Transmigration - Arenas, Jesús; Paganelli, Fernanda L.; Rodríguez-Castaño, Patricia; Cano-Crespo, Sara; van der Ende, Arie; van Putten, Jos P. M.; Tommassen, Jan (Frontiers in Cellular and Infection Microbiology, 2016)
Neisseria meningitidis is a Gram-negative bacterium that resides as a commensal in the upper respiratory tract of humans, but occasionally, it invades the host and causes sepsis and/or meningitis. The bacterium can produce eight autotransporters, seven of which have been studied to some detail. The remaining one, AutB, has not been characterized yet. Here, we show that the autB gene is broadly distributed among pathogenic Neisseria spp. The gene is intact in most meningococcal strains. However, its expression is prone to phase variation due to slipped-strand mispairing at AAGC repeats located within the DNA encoding the signal sequence and is switched off in the vast majority of these strains. Moreover, various genetic disruptions prevent autB expression in most of the strains in which the gene is in phase indicating a strong selection against AutB synthesis. We observed that autB is expressed in two of the strains examined and that AutB is secreted and exposed at the cell surface. Functionality assays revealed that AutB synthesis promotes biofilm formation and delays the passage of epithelial cell layers in vitro. We hypothesize that this autotransporter is produced during the colonization process only in specific niches to facilitate microcolony formation, but its synthesis is switched off probably to evade the immune system and facilitate human tissue invasion.